New global tourism innovation in a post-coronavirus era. Issue 1 (2nd January 2021) - Nunes, Sérgio; Cooke, Philip
ABSTRACT: World capitalism has become capitalism of abundance, but decadent capitalism. Today's capitalism is potentially destructive of the planet on which we live. This text seeks to highlight some of the irrationalities underlying this destructive potential, taking the relation between tourism and innovation as a paradigmatic example. The conceptual, political and operational articulation of tourism with innovation is not an easy task to accomplish, and there are many misunderstandings to block its desired symbiosis. It is also quite clear that innovation, namely that which is mediated and valued solely by market and economic and financial performance criteria, induces production and consumption that have contributed to climate change and levels of unsustainability of the planet. This text has three objectives: to requalify the role of innovation in capitalist society, to reconceptualize the relationship between tourism and innovation and to identify some challenges that will test this relationship in the post-COVID-19 era.